Meningkatkan Fasilitas Akomodasi Objek Wisata Pantai Gamat Melalui Desain Masterplan Penataan - I Kadek Merta Wijaya; I Wayan Jawat; Ni Komang Armaeni; Ni Wayan Meidayanti mustika (Fakultas Teknik Universitas Warmadewa, 2024)
Nusa Penida Island tourist attractions have exotic natural characteristics of beaches and hills. This potential is evenly distributed in the northern part of the coast and the southern part of Nusa Penida. The unavailability of tourist support facilities has an impact on the comfort and accessibility that is not optimal towards these tourist attractions. The picture can be seen on the Gamat Beach tourist attraction which is located in the western part of the coast of Nusa Penida. Gamat Beach is one of the diving spots in Nusa Penida which has the potential for the beauty of coral reefs and fish as a tourist attraction on the beach. Currently, tourists have access to Gamat Beach by sea and to access the beach, there are no supporting facilities or infrastructure. Therefore, it is very difficult for tourists to enjoy the beauty of Gamat Beach optimally. In addition, Gamat Beach began to be eroded by coastal waves and it was feared that the coastline with beach sand would be eliminated. The purpose of this activity is to produce a master plan for the arrangement of facilities at Gamat Beach tourist attraction in an effort to support tourist activities at the tourist attraction. The methods used in this service activity are mapping, conceptual, induction (design), and focus group discussion. The results of this service activity are in the form of a design of a master plan for the arrangement of Gamat Beach tourist objects.